Interface Design in System of Systems Engineering: Enhancing a Sustainable Circular Economy through Interoperable Business Models - Mennenga, Mark; Dormeier, Christopher; Ghazanfarpour, Zahra; Niemeyer, Jan Felix; Süß, Sandro; Asghari, Reza (Procedia CIRP, 2025)
Circular Economy (CE) addresses resource scarcity and climate change, requiring collaboration among stakeholders in a dynamic and multi-faceted business environment, which can be understood as a System of Systems (SoS). To ensure seamless interactions and interoperability, a key challenge is designing the SoS architecture, particularly the interfaces between interconnected business models. This research highlights the importance of interface design in SoS Engineering (SoSE) to enable desirable emergent functionalities, like circularity. We conduct a systematic literature review to identify key interoperability and interface design approaches, proposing a contract-based, multi-level, multi-perspective framework to support circular system engineering. The case of a CE of photovoltaic panels illustrates the potential benefits for the engineering of circular systems and the business model design of a focal company.